Mucosa-associated invariant T cells link intestinal immunity with antibacterial immune defects in alcoholic liver disease. Issue 5 (2nd November 2017) - Riva, Antonio; Patel, Vishal; Kurioka, Ayako; Jeffery, Hannah C; Wright, Gavin; Tarff, Sarah; Shawcross, Debbie; Ryan, Jennifer M; Evans, Alexander; Azarian, Sarah; Bajaj, Jasmohan S; Fagan, Andrew; et al.
Abstract : Background/aims: Intestinal permeability with systemic distribution of bacterial products are central in the immunopathogenesis of alcoholic liver disease (ALD), yet links with intestinal immunity remain elusive. Mucosa-associated invariant T cells (MAIT) are found in liver, blood and intestinal mucosa and are a key component of antibacterial host defences. Their role in ALD is unknown. Methods/design: We analysed frequency, phenotype, transcriptional regulation and function of blood MAIT cells in severe alcoholic hepatitis (SAH), alcohol-related cirrhosis (ARC) and healthy controls (HC). We also examined direct impact of ethanol, bacterial products from faecal extracts and antigenic hyperstimulation on MAIT cell functionality. Presence of MAIT cells in colon and liver was assessed by quantitative PCR and immunohistochemistry/gene expression respectively. Results: In ARC and SAH, blood MAIT cells were dramatically depleted, hyperactivated and displayed defective antibacterial cytokine/cytotoxic responses. These correlated with suppression of lineage-specific transcription factors and hyperexpression of homing receptors in the liver with intrahepatic preservation of MAIT cells in ALD. These alterations were stronger in SAH, where surrogate markers of bacterial infection and microbial translocation were higher than ARC. Ethanol exposure in vitro, in vivo alcohol withdrawal and treatment with Escherichia coli had no effect on MAIT cell frequencies, whereas exposure to faecal bacteria/antigens induced functional impairments comparable with blood MAIT cells from ALD and significant MAIT cell depletion, which was not observed in other T cell compartments. Conclusions: In ALD, the antibacterial potency of MAIT cells is compromised as a consequence of contact with microbial products and microbiota, suggesting that the 'leaky' gut observed in ALD drives MAIT cell dysfunction and susceptibility to infection in these patients.